Study of thermal migration and induced mechanical effects in double U-tube energy piles - Luo, Jin; Zhao, Haifeng; Gui, Shuqiang; Xiang, Wei; Rohn, Joachim (Computers and Geotechnics, 2017)
This paper investigates two geothermal energy piles using thermal response tests (TRTs). A set of parameters including pile wall temperature, ground temperature and strain are monitored at four different depths. The thermally induced mechanical behavior of the energy piles are then analyzed based on the monitoring data. The results show the following: (1) The temperature at the pile wall clearly varies throughout the heating and cooling cycle, and the ground temperature distribution shows a delay compared to the TRT stages. (2) The thermally induced mechanical effects are influenced by both the temperature and restraint conditions. © 2017 Elsevier Ltd
Keywords: Geothermal energy; Energy piles; Ground temperature; Heating and cooling cycles; Mechanical behavior; Mechanical effects; Restraint conditions; Thermal migration; Thermal response test; Piles; cooling; geothermal energy; heating; mechanical property; pile response; strain; temperature effect